Paper 75: Development and Validation of the KOOS-ACL: A Short-form Version of the KOOS for Young Patients with ACL Tears. Issue 7 (30th July 2022) - Tremblay, Paul; Getgood, Alan; Bryant, Dianne; Marmura, Hana
Objectives: To develop and validate a short form, disease-specific version of the KOOS appropriate for the young active ACL deficient population: the KOOS-ACL. Methods: A baseline dataset of 605 young patients (< 25 years) with ACL tears was divided into a development and validation sample. Exploratory factor analyses were conducted in the development sample to identify the underlying factor structure and reduce the number of KOOS items based on statistical and conceptual indicators. Confirmatory factor analyses were conducted to check fit indices of the proposed KOOS-ACL model in both samples. Structural validity, reliability, and responsiveness to change were assessed in the full sample at five timepoints: baseline and 3 months, 6 months, 12 months and 24 months post-operatively. Results: Two factors were deemed most appropriate for the KOOS-ACL: Functionality and Sport. Fifteen items were removed from the full length KOOS based on discriminant validity (i.e., lack of distinctiveness between some proposed constructs) and another fifteen items were removed for repetitive content. The final KOOS-ACL model showed acceptable structural validity (CFI and TLI > 0.9, RMSEA and SRMR < 0.08), internal consistency reliability (a > 0.8), and responsiveness to change (effect size > 0.8) at all five timepoints in the dataset. The KOOS-ACL showed strong and significant correlations to the original KOOS and IKDC at all timepoints (r > 0.7). Conclusions: The new KOOS-ACL questionnaire contains 12 items and two subscales relevant to young active ACL patients. The KOOS-ACL would reduce patient burden by more than two thirds and provides improved structural validity compared to the full length KOOS while maintaining adequate psychometric properties and relatedness to other popular outcome measures currently used following ACL injuries. The KOOS-ACL may be a more relevant outcome to use with young active ACL patients within the two years of surgery.